Innovation Management and the Purposive Design of Diffusion Processes - Fritzsche, Albrecht (Diffusive Spreading in Nature, Technology and Society, 2023)
The chapter gives insight into the efforts that are undertaken by innovation management to ensure that diffusion processes can be systematically planned and controlled. Using examples from manufacturing, telecommunications and civil engineering, the chapter shows that the conditions under which innovations spread through business and society are not predetermined. They can be altered in a variety of ways, which enables innovation management to interfere not only with the speed and direction of diffusion processes, but also with its subject matter and the roles of the actors that are involved. In line with the spatial turn of business and management studies, this can be interpreted as a purposive design of the topological structures underlying diffusion models to avoid complexity.<br